Lactoferrin a multiple bioactive protein: An overview - García-Montoya, Isui Abril; Cendón, Tania Siqueiros; Arévalo-Gallegos, Sigifredo; Rascón-Cruz, Quintín (Biochimica et biophysica acta, 2012)
Lactoferrin (Lf) is an 80kDa iron-binding glycoprotein of the transferrin family. It is abundant in milk and in most biological fluids and is a cell-secreted molecule that bridges innate and adaptive immune function in mammals. Its protective effects range from anticancer, anti-inflammatory and immune modulator activities to antimicrobial activities against a large number of microorganisms. This wide range of activities is made possible by mechanisms of action involving not only the capacity of Lf to bind iron but also interactions of Lf with molecular and cellular components of both hosts and pathogens. This review summarizes the activities of Lf, its regulation and potential applications. The extensive uses of Lf in the treatment of various infectious diseases in animals and humans has been the driving force in Lf research however, a lot of work is required to obtain a better understanding of its activity. The large potential applications of Lf have led scientists to develop this nutraceutical protein for use in feed, food and pharmaceutical applications. This article is part of a Special Issue entitled Molecular Mechanisms of Iron Transport and Disorders. ► It is well known that the mechanisms of action of antimicrobial activity are not fully understood. ► Important advances were made in heterologous Lf expression in prokaryotic systems. ► In the near future we will see the exploitation of the full capacity of lactoferrin expression in plants.